KARAKTERISASI TOKOH DALAM NASKAH DRAMA SANDAL JEPIT KARYA HERLINA SYARIFUDIN - Ahmad Arif Kurniawan; Hidayah Budi Qur’ani (Haluan Sastra Budaya, 2020)
This study aims to describe the characterization of the characters in Herlina Syarifudin's Sandal Jepit drama script (2006). The data in this study were taken from quotations from character dialogues in the Sandal Jepit drama script. The method used is descriptive qualitative. The results show that (1) characterization of the characters is clearly described by the author that Joko, Peggy, and Lala are the main characters in this drama script, (2) the character of the Mascot character is a dynamic character and brings changes to the story.